Monetary Neutrality in the Nepalese Economy during 1975-2008 - Khanal, Mukesh (NRB Economic Review, 2011)
One of the methods of measuring the effectiveness of monetary policies is via inspection of monetary neutrality in the economy. It is a concept from classical economics and it suggests that changes in nominal variables do not have any impact on real variables. This paper studies the presence or absence of effective monetary policy in Nepal between 1975 and 2008 by observing money supply (nominal side), and real GDP (real). Results suggest that an increase in money supply immediately lowers the real GDP in the short run, but has no effect on real GDP in the long run. This evidence suggests that Nepal Rastra Bank’s monetary policies between 1975 and 2008 may have been counter-productive in the short-run, but they were effective for long-run growth and stability of the Nepalese economy.